Supervision System of Communication Project Procurement - Youli Huang (Dianxin kexue)
Communication engineering procurement is one of the largest risks in the communication engineering construction.Combining working practice，the main risk points in communication engineering procurement were analyzed，and the difficulties in communication engineering procurement supervision were also proposed.Based on the theoretical model of the risk prevention and control，the process supervision and risk prevention and control mechanism of communication engineering procurement were studied.